The Suitability of Limestone from Pilaspi Formation (Middle-Late Eocene) for Building Stone in Koya Area, NE Iraq - Omar, Hemn M.; Ismail, Nawzat R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
Suitability of limestone rocks has a crucial importance when stones are used for constructing modern structure. The purpose of this study is to clarify the links between physical, mechanical properties of limestone rocks, also their quality to use as building materials. A total of six limestone rock samples were collected from three different outcrops locations within Pilaspi Formation in Koya area. Engineering geological and geotechnical properties of the limestone rocks in the study area were determined based on the field studies and laboratory tests. The field studies included observations/ measurements of rock mass characteristics such as color, grain size, orientation, bedding thickness and weathering state of the rock materials also spacing, persistence, roughness and infilling material of the discontinuities. Laboratory tests were carried out for determining water content, water absorption, density, uniaxial compressive strength, slake durability and porosity of the rock materials. The study results go well with the national and international standards (Iraqi Standards, 1989; American Society for Testing and Materials, 2004; International Society for Rock Mechanics, 1981) and have shown that the limestone rocks are acceptable for building stone.